Simulasi Perencanaan Jaringan Transport Metro Ethernet Menggunakan Aplikasi Cisco Packet Tracker Pada Perusahaan Antar Cabang - Utami Pingkan Anggraini; Yogi Ramadani; Adi Pramono; Didik Aribowo (Lembaga Pengembangan Kinerja Dosen, 2023)
Metro ethernet is basically a large-scale data communication network, meaning that it can reach a large city using ethernet technology that is able to cover large distances equipped with various functions found on ethernet networks. Cisco packet tracker is a network simulation software issued by Cisco system that functions as a medium for learning, training and simulation research on computer networks. Therefore the authors simulated the design of the metro ethernet transport network using the Cisco Packet Tracker software application. The method used is descriptive method with data collection techniques in the form of literature studies by utilizing reading sources as a bibliography from the internet such as journals and books as well as designs made using the Cisco packet tracker software application